Age and Type of Delivery as Risk Indicators for Maternal Mortality - Oliveira, Isabella Mantovani Gomes Dias de; Fonseca, Emílio Prado da; França, Fabiana Mantovani Gomes; Cortellazzi, Karine Laura; Pardi, Vanessa; Pereira, Antonio Carlos; Tagliaferro, Elaine Pereira da Silva (Revista Brasileira de Ginecologia e Obstetrícia / RBGO Gynecology and Obstetrics, 2023)
Objective: This study assessed maternal mortality (MM) and related factors in a large-sized municipality in the Southeastern region of Brazil (Campinas, São Paulo) during the period 2000-2015.Methods: This study consisted of two phases: 1. An analytical nested case-control phase that assessed the impact of individual and contextual variables on MM; and 2. an ecological phase designed to contextualize maternal deaths by means of spatial analysis. The case group consisted of all maternal deaths (n = 87) and the control group consisted of 348 women who gave birth during the same period. Data analysis included descriptive statistics, association, and multiple logistic regression (MLR) tests at p < 0.05 as well as spatial analysis.Results: Maternal Mortality Ratio was 37 deaths per 100.000 live births. Deaths were dispersed throughout the urban territory and no formation of cluster was observed. MLR showed that pregnant women aged ≥ 35 years old (OR = 2.63) or those with cesarean delivery (OR = 2.51) were more prone to maternal death.Conclusion: Maternal deaths were distributed dispersedly among the different socioeconomic levels and more prone to occur among older women or those undergoing cesarean deliveries.
Keywords: Maternal mortality; Observational study; Socioeconomic factors